Analytical model of residual stress in ultrasonic rolling of 7075 aluminum alloy. (August 2022) - Zheng, Jianxin; Shang, Yingju; Guo, Yonglei; Deng, Hanlin; Jia, Liuyin
Abstract: Ultrasonic rolling produces large values of residual compressive stress (RCS) in the surface layer of metal part, thereby significantly enhancing the fatigue resistance of the part. Ultrasonic rolling is a complex elastic-plastic deformation process, and it is difficult to accurately predict the residual stress produced by ultrasonic rolling. 7075 aluminum alloy was processed in this work. The elastic-plastic deformation caused by "loading-unloading" during ultrasonic rolling was analyzed based on Hertzian theory and elastic-plastic deformation theory. The residual stress model of ultrasonic rolling was developed by considering the effects of initial surface residual stress and plastic indentation depth. Finally, the model was verified by experiments. The numerical analysis results show that the surface RCS, the value and depth of the maximum RCS and thickness of the RCS layer increase to different degrees with the increment of the static load, the amplitude and the roller radius. The trend of the experimentally obtained surface RCS value with static load is consistent with that of the numerical calculations. The surface RCS increase with the increasing of the static load. The maximum error between the calculated RCS and the experimental result is no more than 10 %. The proposed residual stress model in ultrasonic rolling is relatively reliable.